International financial integration and national price levels: The role of the exchange rate regime - Mathias Hoffmann; Peter Tillmann (Philipps-University Marburg, Faculty of Business Administration and Economics, 2011)
How does international financial integration affect national price levels? Panel evidence for 54 industrialized and emerging countries shows that a larger ratio of foreign assets and liabilities to GDP, our measure of international financial integration, increases the national price level under fixed and intermediate exchange rate regimes and lowers the price level under floating exchange rates. This paper formulates a two-country open economy sticky-price model under either segmented or complete asset markets that is able to replicate these stylized facts. It is shown that the effect of financial integration, i.e. moving from segmented to complete asset markets, is regime-dependent. Under managed exchange rates, financial integration raises the national price level. Under floating exchange rates, however, financial integration lowers national price levels. Thus, the paper proposes a novel argument to rationalize systematic deviations from PPP.
Keywords: F21; F36; F41; 330; international financial integration; exchange rate regime; national price level; PPP; foreign asset position